A Novel all Solid-State Contact PVC-Membrane Beryllium-Selective Electrode Based on 4-Hydroxybenzo-15-Crown-5 Ether Ionophore - Isildak, Ibrahim; Attar, Azade; Demir, Ersin; Kemer, Baris; Aboul-Enein, Hassan Y. (BENTHAM SCIENCE PUBL LTD, 2018)
Aim: A novel all solid-state contact PVC-membrane beryllium-selective electrode based on 4-hydroxybenzo-15-crown-5 ether as an ionophore is described. Results: The best performance was obtained with a membrane composition of 4% ionophore, 67% dioctyl sebacate (DOS), 28% poly(vinyl chloride) (PVC), and 1% potassium tetrakis (p-chloro) phenylborate (KTClPB) (w/w). The all solid-state contact PVCmembrane beryllium-selective electrode together with an Ag/AgCl reference electrode exhibited sub-Nernstian response with a slope of 22 +/- 1 mV/decade to beryllium ions from 1.0x10(-6) to 1.0x10(-1) M, and resulted a considerably low detection limit of 6.2x10(-7). The electrode had a good performance in selectivity over a wide range of interfering cations tested. It showed a working pH range between 4.0-8.2 with fast response time (< 10 s) and a good reproducibility. Conclusion: The all solid-state contact PVC-membrane beryllium-selective electrode developed was successfully applied in potentiometric titration of Be2+ ions with EDTA.
Keywords: Beryllium-selective electrode; 4-hydroxybenzo-15-crown-5 ether; potentiometry; PVC membrane; ionophore; EDTA; ATOMIC-ABSORPTION-SPECTROMETRY; ULTRA-TRACE BERYLLIUM; POTENTIOMETRIC SENSOR; DOUBLE HYDROXIDE; WATER SAMPLES; BE2+ ION; EXTRACTION; MAGNESIUM; PLASMA; SPECTROPHOTOMETRY; Chemistry